2018
DOI: 10.1002/da.22735
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional outcomes of cannabis use among individuals with anxiety disorders: A 3‐year population‐based longitudinal study

Abstract: These findings add to previous reports suggesting that poorer outcome of anxiety disorders among cannabis users may be attributed mainly to differences in baseline factors and not cannabis use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 85 publications
(104 reference statements)
0
9
0
Order By: Relevance
“… 2409 participants N/A Almost 62% of CBD users reported using CBD to treat a medical condition. The top three medical conditions were pain, anxiety, and depression Feingold et al 2018 [ 58 ] Data was drawn from Waves 1 and 2 of the National Epidemiologic survey on Alcohol and Related Conditions 3723 participants N/A Remission rates for non-users: 66.0% Remission rates for users: 52.8%) Cuttler et al 2018 [ 57 ] Data from the cannabis tracking app Strainprint TM 5085 tracking sessions Inhalation (smoking, vaping, concentrates, dab bubbler, dab portable) 93.5% of sessions recorded decrease in anxiety …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 2409 participants N/A Almost 62% of CBD users reported using CBD to treat a medical condition. The top three medical conditions were pain, anxiety, and depression Feingold et al 2018 [ 58 ] Data was drawn from Waves 1 and 2 of the National Epidemiologic survey on Alcohol and Related Conditions 3723 participants N/A Remission rates for non-users: 66.0% Remission rates for users: 52.8%) Cuttler et al 2018 [ 57 ] Data from the cannabis tracking app Strainprint TM 5085 tracking sessions Inhalation (smoking, vaping, concentrates, dab bubbler, dab portable) 93.5% of sessions recorded decrease in anxiety …”
Section: Resultsmentioning
confidence: 99%
“…In a 3-year longitudinal survey of cannabis use by patients with a primary anxiety disorder diagnosis (N = 3723), it was found that remission rates from anxiety disorders were higher among cannabis nonusers (Table 2). However, these differences were not statistically significant in adjusted models [58]. Discrepancies in responses are further highlighted as men reported experiencing greater headache/migraine relief from medical cannabis than women, despite a larger proportion of women reporting using it for this reason.…”
Section: Epidemiological Datamentioning
confidence: 91%
“…However, a stronger positive association was revealed between anxiety and cannabis use disorder. Other longitudinal data involving the USA-based National Epidemiologic survey on Alcohol and Related Conditions [37] confirms there is no obvious causal inference. The study included individuals with a diagnosis of any anxiety disorder during the initial 4-year data collection period, comparing cannabis nonusers to users, and also individuals with cannabis use disorder at a later time point on a range of psychosocial measures.…”
Section: Affective Disorders Anxietymentioning
confidence: 98%
“…However, new research in this area is limited. Only one recent article examined QOL related to substance use in anxiety, finding that individuals with anxiety disorders who used cannabis (but did not meet criteria for cannabis use disorder) reported poorer QOL than non-cannabis users in the areas of mental health and role functioning, but noncannabis users did not differ in QOL compared to those with comorbid cannabis use disorder [47]. Future research should consider substance type, frequency, and purpose of use in understanding substance use behaviors as a correlate of QOL in anxiety disorders.…”
Section: Substance Use Behaviorsmentioning
confidence: 99%